Answer:
2. x² + 8y²
3. -6
- 2y³ + 10y²
4. 3a² - 2a
Explanation:
2. Two minuses make a plus.
(10x² + 4y²) - (9x² - 4y²) = 10x² + 4y² - 9x² + 4y²
Evaluate like terms.
10x² + 4y² - 9x² + 4y² = x² + 8y²
3. When multiplying terms in a bracket, you must multiply the term outside the bracket to all the terms in the bracket.
-2y²(3y² + y - 5) = (-2y² × 3y²) + (-2y² × y) + (-2y² × -5)
= (-6
) + (-2y³) + (10y²)
= -6
- 2y³ + 10y²
4. When dividing terms in a bracket, you must divide all the terms in the bracket to the term outside the bracket.
(12
- 8a³) ÷ 4a² = (12
÷ 4a²) + (- 8a³ ÷ 4a²)
= (3a²) + (-2a)
= 3a² - 2a